Faktor Risiko Penyakit Ginjal Kronik Diabetes (PGK-DM) pada Diabetes Mellitus Tipe-2 (Studi di RSUD DR Soedarso Kota Pontianak Provinsi Kalimantan Barat) - Rini, Sulistio; Hadisaputro, Suharyo; Lestariningsih, Lestariningsih; Nugroho, Heri; Budijitno, Selamat (Sekolah Pascasarjana Universitas Diponegoro Semarang, 2018)
Background: Prevalence of type-2 diabetes mellitus have increased signiï¬cantly. The increasing number of people with diabetes has a major impact on the development of chronic diabetic kidney disease. The research was aimed to clarify several risk factors of chronic diabetic kidney disease on type-2 diabetes mellitus (CDK-DM).Method: The research was based on case control study design. The number of respondents was 140 respondents consisting 70 cases and 70 controls that met the criteria of inclusion and exclusion. The cases were patients with type-2 chronic diabetic kidney disease stadium 2-5. The controls were patients with type-2 chronic diabetic kidney disease with blood sugar levels â¥ 200 mg/dL. The data were then analyzed using logistic regression.Results: The result shows that risk factors of chronic diabetic kidney disease in type-2 diabetes mellitus are diabetes in family (OR = 6,732; 95% CI = 2,623- 17,276), high blood pressure (OR =6,760; 95% CI = 2,190- 20,867), lack of physical activities (OR = 4,367 95% CI = 1,823-10,462) and lack of family support (OR = 4,203; 95% CI = 1,437-12,295). The probability of chronic diabetic kidney disease occurrence in type-2 diabetes mellitus when four risk factors exist are96,71%.Conclusion: The host factors have important role of chronic diabetic kidney disease in type 2 diabetes mellitus . The factors proven to be risk factors for occurrence of chronic diabetic kidney disease in type 2 diabetes mellitus were diabetic in the family, Hipertension, poor physical exercise and family Support.